Pengaruh Pengalaman Kerja, Uang Saku,Penghasilan Orang Tua Terhadap Pengelolaan Keuangan Mahasiswa Dengan Literasi Keuangan Sebagai Variabel Intervening ( Studi Kasus Mahasiswa Universitas Teknologi Muhammadiyah Jakarta) - Alvina Maharani; Heri Ispriyahadi (Jurnal Ragam Pengabdian, 2026)
Effective financial management is an essential competency for university students in making sound financial decisions. This study aims to analyze the direct and indirect effects of work experience, allowance, and parental income on students' financial management, with financial literacy serving as an intervening variable. This study employed a quantitative approach involving 153 active students of Muhammadiyah University of Technology Jakarta selected through purposive sampling. Data were collected using a questionnaire that had met the validity and reliability requirements and were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4. The results indicate that work experience, allowance, and parental income have a positive and significant effect on financial literacy. Furthermore, allowance and parental income have a positive and significant effect on students' financial management, whereas work experience has no significant effect. Financial literacy significantly mediates the relationship between allowance and parental income and students' financial management, but it does not mediate the relationship between work experience and students' financial management. These findings highlight the important role of financial literacy in strengthening students' financial management, particularly through the influence of allowance and parental income.